Association between red blood cell distribution width and blood transfusion in patients undergoing living donor liver transplantation: Propensity score analysis. (10th May 2022) - Sim, Ji‐Hoon; Kwon, Hye‐Mee; Jun, In‐Gu; Kim, Sung‐Hoon; Kim, Bomi; Kim, Sehee; Song, Jun‐Gol; Hwang, Gyu‐Sam
Abstract: Background: Living donor liver transplantation (LDLT) has been associated with massive transfusion. However, information on indicators predicting transfusion in LDLT is limited. This study investigates the association between red blood cell distribution width (RDW) and intraoperative transfusion in LDLT recipients. Methods: This study analyzed 2546 patients who underwent LDLT between January 2010 and October 2019. The patients were divided into two groups based on preoperative RDW cutoff level (<14.4 and ≥14.4). We performed multivariate regression analysis to assess the association between RDW and intraoperative transfusion. We also performed propensity score matching analysis to compare the incidence of intraoperative transfusion between the two groups. The predictive power of RDW was assessed through receiver operating characteristic (ROC), integrated discrimination improvement (IDI), and net reclassification improvement (NRI) analysis. Results: In the multivariate logistic analysis, RDW ≥ 14.4 was significantly associated with intraoperative transfusion (adjusted odds ratio [OR]: 1.53, 95% confidence interval [CI]: 1.13‐2.06, P = .005). There were significant differences in incidence of intraoperative transfusion between the two groups before (54.1% vs 91.6%, P < .001) and after (71.6% vs 79.8%, P = .004) matching. RDW had predictive power for intraoperative transfusion ( P < .001 in NRI, P = .035 in IDI). Conclusions: Preoperative RDW is a potential predictor of intraoperative transfusion in LDLT recipients. Abstract : Sim and colleagues found that red blood cell distribution width ≥14.4 was associated with a higher incidence of intraoperative blood transfusion in living donor liver transportation recipients before and after propensity score matching. Inclusion of red blood cell distribution width in the transfusion model had predictive power for intraoperative transfusion.